The Unexpected Advantages of Using D-Amino Acids for Peptide Self- Assembly into Nanostructured Hydrogels for Medicine - Melchionna, Michele; E. Styan, Katie; Marchesan, Silvia (Current Topics in Medicinal Chemistry, 2016)
Self-assembled peptide hydrogels have brought innovation to the medicinal field, not only as responsive biomaterials but also as nanostructured therapeutic agents or as smart drug delivery systems. D-amino acids are typically introduced to increase the peptide enzymatic stability. However, there are several reports of unexpected effects on peptide conformation, self-assembly behavior, cytotoxicity and even therapeutic activity. This mini-review discusses all the surprising twists of heterochiral self-assembled peptide hydrogels, and delineates emerging key findings to exploit all the benefits of D-amino acids in this novel medicinal area.
Keywords: Heterochiral